Microbiological Detection of Some Pathogenic Bacteria in Diabetic Foot Ulcers of Type 1 and 2 Diabetic Mellitus Patients - Marwah M. AL-Sahi; May Mohammed Ali; Sawsan M. Jabbar AL-Hasnawi (University of Thi-Qar Journal of Science, 2023)
Globally, diabetes mellitus (DM) is a serious health issue. Different aerobic bacteria, that can colonize DFUs including Gram positive cocci, such as Staphylococcus aureus, and (beta-haemolytic) Streptococcus. Coagulation-negative Staphylococcus (CNS), Corynebacterium, Enterococcus, and Cutibacteria are frequently found in ulcer cultures in clinical practice; Gram-negative bacteria account for about one third of DFIs. About 70 participants in all, including 29 individuals with type 1 diabetes and 41 patients with type 2 diabetes who have diabetic foot ulcers. The aims of study: is detecting of some aerobic of pathogenic bacteria in diabetic foot ulcers. Scarping of ulcers takes place after regular saline wound cleansing to eliminate surface pollutants, and then exudate is sampled. Pus, or discharges from the base of the ulcer, is then submitted to the laboratory as quickly as possible using an aseptic approach. Then, the bacteria were inoculated onto various culture media, such as MacConkey and Blood agar as enrichment media, and incubated aerobically at 37°C for 24 hours to isolate aerobic bacteria. The following day, the bacteria were checked for growth, and a pure colony was then prepared. According to morphological examination of bacteria in the culture, microscopic examination of slides, and particular cards of the automated VITEK2 system, isolated bacteria were identified. Results: based on the bacteriological profile of diabetic foot ulcers, S. aureus among the gram-positive isolates and E. coli among the gram-negative isolates were the predominant pathogens. In recommendations, further studies are needed for isolation and identification of another microorganism such as anaerobic bacteria,